ATLAS Electron and Photon Trigger - Hoya, Joaquín (2018)
ATLAS electron and photon triggers covering transverse energies from 5 GeV to several TeV are essential to record signals for a wide variety of physics: from the Standard Model processes to searches for new phenomena. To cope with ever-increasing luminosity and more challenging pile-up conditions at a centre-of-mass energy of 13 TeV, the trigger selections need to be optimized to control the rates and keep efficiencies high. The ATLAS electron and photon trigger in Run-2 is presented, including new techniques developed to maintain their high performance even in high pile-up conditions as well as the first efficiency measurements from the 2018 data taking.